Polymicrobial multidrug-resistant bacteria isolated from street vended fresh fruit juices in Pakistan: A preliminary study. Issue 6 (11th June 2018) - Siddique, Muhammad Hussnain; Qamar, Muhammad Usman; Hayat, Sumreen; Aslam, Bilal; Nadeem, Habibullah; Hussain, Sabir; Saqalein, Muhammad; Saeed, Javeria; Muzammil, Saima
Abstract : Purpose: The purpose of this paper is to evaluate the prevalence and antibiograms of bacteria isolated from various fresh fruit juices at a local market in Faisalabad. Design/methodology/approach: Fresh fruit juice samples ( n =125) were randomly collected using aseptic technique. Each sample (10 mL) was serially diluted with 90 mL of sterile peptone water, from 1×10 −1 to 1×10 −5 . Each dilution was then used to inoculate nutrient agar by surface spread plating. Aerobic colony counts (ACCs) were determined by colony counting. The isolates were sub-cultured on blood and MacConkey agar. Preliminary identification was achieved on the basis of colony morphology and culture characteristic, and confirmed by API® 20E, 20NE, and API® Staph testing. Antimicrobial susceptibility testing was carried out using the Kirby-Bauer disk diffusion assay, per CLSI 2015 guidelines. Findings: The mean ACC ranged from 2.0×10 6 CFU/mL to 4.93×10 6 CFU/mL, with the highest ACC determined for orange juice. Overall, 153 polymicrobial were identified in 125 samples; 103 of these were Gram-negative rods (GNR) and 28 were Gram-positive cocci (GPC). Escherichia coli ( n =38), Klebsiella pneumoniae ( n =32) and Pseudomonas aeruginosa ( n =24) were the predominant GNR; Staphylococcus aureus ( n =28) was the predominant GPC. Antibiogram analysis revealed that all GNR were resistant to ampicillin. However, most E. coli isolates were resistant to ceftazidime (72.4 percent of isolates), and ceftriaxone and cefepime (68.9 percent), while most K. pneumoniae isolates were resistant to cefepime (72 percent) and ceftriaxone (64 percent). All S. aureus isolates were resistant to penicillin, while most (64 percent) were resistant to piperacillin; the most effective drugs against bacteria were vancomycin and imipenem. Practical implications: The findings suggest that the local government regulatory food and public health authorities should take immediate emergency measures. Appropriate surveillance studies and periodic monitoring of food items should be regularly performed to safeguard public health. Originality/value: The current study revealed the prevalence of multidrug-resistant bacteria in freshly prepared fruit juices sold by local street vendors.